2018
DOI: 10.1371/journal.pone.0205663
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure prophylaxis among men who have sex with men in the Amsterdam Cohort Studies: Use, eligibility, and intention to use

Abstract: ObjectiveCurrently, HIV pre-exposure prophylaxis (PrEP) is not covered by health insurance in the Netherlands. We examined time trends in use of PrEP, characteristics of PrEP users, PrEP eligibility and intention to use PrEP among HIV-negative men who have sex with men (MSM) participating in the Amsterdam Cohort Studies (ACS).DesignProspective cohort study.MethodsWe used data from four 6-monthly questionnaire waves, collected between 2015–2017. PrEP use over time was examined in logistic regression models usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 12 publications
3
24
0
Order By: Relevance
“…Regarding the type of PrEP use, previous studies in Belgium, the Netherlands and Australia found that between 23.5% and 48% of the participants preferred non-daily PrEP [12,[28][29][30][31]. A single-centre study in France found the preference for on-demand PrEP to be as high as 75.6% [9].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the type of PrEP use, previous studies in Belgium, the Netherlands and Australia found that between 23.5% and 48% of the participants preferred non-daily PrEP [12,[28][29][30][31]. A single-centre study in France found the preference for on-demand PrEP to be as high as 75.6% [9].…”
Section: Discussionmentioning
confidence: 98%
“…Potential applicants interested in PrEP could have perceived their chance of inclusion as low and thus were discouraged from participating, implying that the number of those actually interested in initiating PrEP in Amsterdam are higher than the number of applicants to the AMPrEP project. Currently, few data on intention to use PrEP in the Netherlands have been published and only crude estimates of the number of MSM willing to take PrEP are available .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these developments, PrEP uptake has been slow. As for the Netherlands, a recent estimation showed that only a small proportion of PrEP‐eligible MSM actually used PrEP in 2017 .…”
Section: Introductionmentioning
confidence: 99%